2003
DOI: 10.1002/pssb.200303279
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oxygen on luminescence and vibrational spectra of Mg‐doped GaN

Abstract: Mg-doped GaN epilayers are analyzed by Raman and low-energy electron-excited nanoluminescence (LEEN) spectroscopies before and after oxygen ambient annealing at temperatures from 450 to 550 °C. Annealing as low as 450 °C shows the appearance of a local vibrational mode of the Mg Ga acceptor. Correspondingly, LEEN emission at 2.8 eV increases and that at 3.27 eV decreases after annealing in oxygen ambient. On the other hand, electron beam treatment decreases 2.8 eV emission and increases 3.27 eV emission. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Another additional band A X observed at around 425 cm −1 is assigned to the vibration of Mg–O and the assignment is supported by the presence of Mg‐related secondary phase in the prepared samples from XRD studies . Figures and depicts reasonable enhancement in the area under the curve for the LVM generated from the replacement of Zn with Mg in the ZnO lattice which can leads to the increased availability of Zn‐related defects (higher number of Zn vacancies/interstitial Zn) . This supports the observed enhancement in the luminescence related to these defect centers after Mg doping from PL studies.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Another additional band A X observed at around 425 cm −1 is assigned to the vibration of Mg–O and the assignment is supported by the presence of Mg‐related secondary phase in the prepared samples from XRD studies . Figures and depicts reasonable enhancement in the area under the curve for the LVM generated from the replacement of Zn with Mg in the ZnO lattice which can leads to the increased availability of Zn‐related defects (higher number of Zn vacancies/interstitial Zn) . This supports the observed enhancement in the luminescence related to these defect centers after Mg doping from PL studies.…”
Section: Resultssupporting
confidence: 72%
“…The additional band A L (~555 cm −1 ) arising after Mg doping identified from the fitted FTIR data can be assigned as Mg‐related LVM . Another additional band A X observed at around 425 cm −1 is assigned to the vibration of Mg–O and the assignment is supported by the presence of Mg‐related secondary phase in the prepared samples from XRD studies . Figures and depicts reasonable enhancement in the area under the curve for the LVM generated from the replacement of Zn with Mg in the ZnO lattice which can leads to the increased availability of Zn‐related defects (higher number of Zn vacancies/interstitial Zn) .…”
Section: Resultsmentioning
confidence: 71%
“…1b the intensity of the 2.8 eV emission decreased on further increasing the O 2 content in the annealing atmosphere. It was suggested that the number of hydrogen-related deep donors (V N -H) [8,9] decreases because of the following reaction:…”
Section: G H O M G H O -mentioning
confidence: 99%
“…We prepared two samples with different Mg concentrations, 3 × 10 18 and 2 × 10 19 cm −3 . The test structures for Hall measurement were annealed at 550 °C for 10 min in air for the Mg activation 31,32) 100 nm Pd electrodes were deposited and annealed at 400 °C for 5 min in nitrogen for ohmic contacts.…”
mentioning
confidence: 99%